2010
DOI: 10.2478/v10009-010-0015-7
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of freshwater red algae in Europe

Abstract: Of the total number of freshwater red algae (ca. 180 taxa), one third are found in Europe (ca. 60 taxa). Over one third (24 taxa) of European taxa have been found at only one single location or at very few locations. The majority of taxa live in running waters, but some occur in lakes, on wet ground, in hot springs or in garden ponds. Diversity in the Nordic countries of Sweden and Finland seems to be somewhat higher (27 and 28 taxa, respectively) than in the central and southern parts of Europe (e.g.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 11 publications
0
14
0
4
Order By: Relevance
“…Batrachospermum atrum is considered to be rare, although widespread, in Europe (Kwandrans & Eloranta, 2010;Alcaraz et al, 2013) and also appears to be rare in Italy, having been reported only twice previously in the 19th century. The species was first collected in 1862 and voucher specimens distributed in Series I of the Erbario Crittogamico Italiano (as B. tenuissimum Bory, see Cuccuini, 1997).…”
Section: Morphological Findingsmentioning
confidence: 95%
See 2 more Smart Citations
“…Batrachospermum atrum is considered to be rare, although widespread, in Europe (Kwandrans & Eloranta, 2010;Alcaraz et al, 2013) and also appears to be rare in Italy, having been reported only twice previously in the 19th century. The species was first collected in 1862 and voucher specimens distributed in Series I of the Erbario Crittogamico Italiano (as B. tenuissimum Bory, see Cuccuini, 1997).…”
Section: Morphological Findingsmentioning
confidence: 95%
“…Several taxa within this order are considered to be sensitive to human impact and therefore to be reliable ecological bio-indicator species (Rott et al, 1999;Haury et al, 2006). Despite the conservation concern and their role as bio-indicators (Kwandrans & Eloranta, 2010), studies of the diversity and ecology of freshwater red algae are lacking, especially in Italy (Eloranta et al, 2011;Ceschin et al, 2013;Bolpagni et al, 2015).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Em estudos prévios realizados no Brasil e no mundo, resultados semelhantes também foram observados (necchi Júnior 1989, necchi Júnior et al 1999, entwisle & Kraft 1984, eloranta & Kwandrans 1996, Kwandrans & Eloranta 2010, Sheath & Cole 1992. Assim, nossos dados confirmam Skuja (1938), que aponta o gênero Batrachospermum como sendo o melhor representado em número de espécies entre as rhodophyta de água doce.…”
Section: Discussionunclassified
“…The total number of taxa recorded in Northern European countries is higher than that in Centraland South-Europe. In Hungary, nine taxa were reported (Kwandrans and Eloranta 2010), two of these (Batrachospermum ectocarpum Sirodot and B. moniliforme Roth) were found in the springs of the Northern Bakony Mountains (Kol 1968). Additionally, some species (Audouinella ciolacea (Kütz.)…”
Section: Introductionmentioning
confidence: 99%